Theoretical Performance Study of an Indirect- Expansion Solar Assisted Heat Pump - Jassim, Asst. Prof. Dr. Najim Abid; Al-Chlaihawi, Kadhim Kareem (Journal of Petroleum Research and Studies, 2017)
This work presents a theoretical performance study of an indirect- expansion solar assisted heat pump SAHP. The theoretical analysis included a simulation of the IX-SAHP using TRNSYS software. These tests were conducted by varying the controlling parameters to investigate their effects on the thermal performance of the IX-SAHP such as the evaporating and condensing temperatures, compressor speed, refrigerant type and the solar collector area. A significant effect of the compressor speed on the thermal performance of the system is indicated. An increase of compressor speed causes a decrease of coefficient of performance COP. The performance of refrigeration system largely depends upon the characteristics of the refrigerants. COP was affected by the solar collector area and type where the COP increases with increasing collector area, but for a given heating load there is a required minimum solar collector‘s area, also evacuated tube solar collector lead to higher COP than flat plate collector for a given collector area. Compared to the conventional heat pump system, the present indirect expansion solar assisted heat pump system has the advantage that the collector can absorb the radiation and ambient energy and lead to increase the superheat level at the compressor inlet, so that reduced the work input of compressor in comparison to the conventional heat pump system.